2021
DOI: 10.1021/acsami.1c18507
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Activated Carbon for Competing Adsorption of Volatile Organic Compounds and Water

Abstract: The interfacial interaction of activated carbon with volatile organic compounds (VOCs) is seriously affected by water vapor. Therefore, it is vital to enhance the hydrophobic performance of activated carbon for expanding its application in industrial and environmental fields. Herein, a series of hydrophobic activated carbon was fabricated by tailored mixed siloxane and applied in dynamic competitive adsorption at 0, 50, and 90% humidity. Simultaneously, the diffusion molecular models and multicomponent adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Subsequently, trimethoxy (1H,1H,2H,2H‐heptadecafluorodecyl) silane (FAS) hydrolysis and dehydration processes under the catalysis of ammonia through solvothermal method were employed to decorate the surface of Bi NSA. [ 30 , 31 , 32 ] As can be seen in Equations ( 2 ) and ( 3 ), FAS initially underwent the hydrolysis process for the formation of hydroxyl. Then, the consequential dehydration condensation between the hydrolysis products of FAS and the surface hydroxyl of the hydrophilic Bi NSA went on for the formation of aerophilic network.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, trimethoxy (1H,1H,2H,2H‐heptadecafluorodecyl) silane (FAS) hydrolysis and dehydration processes under the catalysis of ammonia through solvothermal method were employed to decorate the surface of Bi NSA. [ 30 , 31 , 32 ] As can be seen in Equations ( 2 ) and ( 3 ), FAS initially underwent the hydrolysis process for the formation of hydroxyl. Then, the consequential dehydration condensation between the hydrolysis products of FAS and the surface hydroxyl of the hydrophilic Bi NSA went on for the formation of aerophilic network.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5b shows the Fourier transform infrared (FT‐IR) spectrum of the two electrodes. Compared with Bi NSA@CF, some significant characteristic absorption peaks at 777, 899, and 971 cm –1 assigned to the Bi—O—Si bond connecting Bi nanosheets and FAS [ 47 , 48 ] and 810, 1074, 1117, and 1146 cm –1 attributed to symmetric, asymmetric and various stretching modes of Si—O—Si links [ 30 , 31 , 49 , 50 , 51 , 52 ] were identified for Bi NSA‐TP@CF electrode. These crisscross connections not only stabilized aerophilic network but also allowed plentiful synergetic sites for protons adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…The hierarchical porous characteristics are further studied by the N 2 adsorption/desorption measurements shown in Figure S3. There is a typical type-IV curve with an H1-type hysteresis loop, suggesting the coexistence of micropores and mesopores. The specific surface areas of DCA, OPCA, HPCA, and OHPCA are 462, 491, 557, and 570 m 2 g –1 , respectively (Table S1). Besides, the pore size distribution was analyzed by using the Drive-Fitness-Technology, shown in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…Adsorption of VOCs from the gas and liquid phases has been the focus of scientific research but often involves only one component. , For single-component experiments, fixed bed adsorption is characterized based on the Thomas, bed depth service time, and Yoon–Nelson models, obtaining a high degree of fit between experimental data and model values. , Studies in the related literature have indicated that during the adsorption of VOC mixtures, competitive adsorption occurs, i.e., a phenomenon involving the displacement of molecules of one adsorbate from the adsorption bed by molecules of another adsorbate. For binary VOC mixtures, the breakthrough curves can be divided into characteristic areas: (1) the outlet concentrations of both components are close to zero; (2) the mass transfer zone of the component with a lower adsorption affinity reaches the outlet of the adsorption column; (3) the outlet concentration of the less adsorbed component exceeds the value of its inlet concentration (displacement from the bed by the component with a higher adsorption affinity); (4) the mass transfer zone of the better-adsorbed component reaches the column outlet, and the outlet concentration of the component increases; and (5) the adsorption bed is completely saturated, and the outlet concentrations are close to the initial concentrations …”
Section: Introductionmentioning
confidence: 99%